Using Social Norms to Increase Behavior Change in Sustainable Landscaping - Laura A. Sanagorski; Paul Monaghan (EDIS)
When Extension agents work to encourage behavioral changes in their community through educational programming, they may already be using some elements of social marketing. Extension educators can use an understanding of their clients’ reservations and inclinations toward a behavior, or their benefits and barriers, to develop strategies that encourage behavior change. Common strategies include prompts and reminders, incentives, and changing social norms. These strategies may be piloted on a small scale, modified if necessary, and then implemented on a large scale and further evaluated. This publication’s purpose is to describe the use of social norms as a social marketing strategy and make recommendations for applying social norms as a tool in Extension programming. This 5-page fact sheet was written by Laura Sanagorski (Warner) and Paul Monaghan, and published by the UF Department of Agricultural Education and Communication, February 2014.